What the fuck do I know? - Sara Hjördís Blöndal 1989- (2023)
In this thesis I look at my theatre making methods and how I translate and transfer them into my Curatorial Practice, focusing on curation as a way of telling stories, and conveying a narrative. In this text I look at my creative process, working rituals and routines, as well as decision making process. This thesis is an attempt to define what my mind knows, why it knows it and how I use that knowledge in my professional work in theatre and museums. I examine the constructions of the White Cube and the Black Box and how I choose to see them and use those human constructions. The text gives insight into my experience as a scenographer in theatre and the theatre practitioners I look to in my practice, Peter Brook, and Alison Oddey. The thesis gives insight into the process of curating the final graduation exhibition And Then a Little Something Occurred that I curated and layered into and onto a permanent exhibition at the Akranes Folk Museum.